Kraft Lignin: From Pulping Waste to Bio‐Based Dielectric Polymer for Organic Field‐Effect Transistors (Adv. Sustainable Syst. 12/2022). (14th December 2022) - D'Orsi, Rosarita; Irimia, Cristian Vlad; Lucejko, Jeannette J.; Kahraman, Bilge; Kanbur, Yasin; Yumusak, Cigdem; Bednorz, Mateusz; Babudri, Francesco; Irimia‐Vladu, Mihai; Operamolla, Alessandra
Abstract : Organic Electronics In article number 2200285, Mihai Irimia‐Vladu, Alessandra Operamolla and co‐workers demonstrate the successful use of kraft lignin, the waste biopolymer produced by pulp mills, as the dielectric material for organic field effect transistors. This work represents an example of a circular economy applied to organic electronics.